2015
DOI: 10.3892/mmr.2015.3634
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the blastocyst quality and efficiency of putative embryonic stem cell line derivation from porcine embryos produced in vitro using a novel culturing system

Abstract: Porcine embryonic stem cells (pESCs) have great potential for application in translational biomedical research, including xenotransplantation and disease models. Obtaining high-quality blastocysts is the most important factor in the isolation and colonization of primary ESCs and the establishment of ESC lines. In pigs, in vitro-derived blastocysts have a limited cell number compared to in vivo-derived blastocysts and show an indefinite inner cell mass, which may result in failure to establish pESC lines. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Also, the derivation efficiency of ESC might be another tool to evaluate blastocysts indirectly [ 56 ]. Some reports have shown that reducing oxidant stress increased the success of establishing new mouse and porcine ESC lines [ 57 , 58 ]. Although further experiments need to be conducted, the putative porcine ESC lines were derived from 100- and 200-µg/ml Ge-132 treatment group and showed a similar derivation process with primed ESCs, such as previously reported porcine ESC lines [ 59 ] as shown in Supplementary Table 1 and Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the derivation efficiency of ESC might be another tool to evaluate blastocysts indirectly [ 56 ]. Some reports have shown that reducing oxidant stress increased the success of establishing new mouse and porcine ESC lines [ 57 , 58 ]. Although further experiments need to be conducted, the putative porcine ESC lines were derived from 100- and 200-µg/ml Ge-132 treatment group and showed a similar derivation process with primed ESCs, such as previously reported porcine ESC lines [ 59 ] as shown in Supplementary Table 1 and Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of resveratrol on a large number of cellular processes allowed us to assume that this promising compound can also be useful in the positive regulation of the fundamental properties of ESCs—self-renewal and pluripotency. In favor of this assumption, there is an evidence that supplementation of resveratrol has beneficial effect on porcine and cow in vitro fertilization and subsequent embryonic development 11,12 . The addition of resveratrol to the medium for cultivation of pig oocytes allows to obtain more viable blastocysts and efficiently isolate ESCs from them 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Improvements to the IVM system will benefit from a range of applications, including animal husbandry and medicine, in addition to the potential use of planned in vitro fertilization, including efficient embryo production, cloning, genetic modification and animal models (de Souza-Fabjan et al, 2014). Compared with other animals, porcine animals have become the model of choice for human transformation studies due to their similarity in body shape and physiological structure (Cheong et al, 2015). Although in vivo embryos are better than in vitro embryos, it is more expensive and laborious to produce embryos in vivo.…”
Section: Introductionmentioning
confidence: 99%